A practical appraisal of thermoelectric materials for use in an autonomous power supply. (November 2019) - Takagiwa, Yoshiki; Shinohara, Yoshikazu
Abstract: We discuss the selection of thermoelectric materials for use in autonomous power supplies for future sensing networks in terms of cost payback time and environmental and material costs, which are critical factors for practical application. Besides cost and the availability of the constituent elements, suitable thermoelectric materials need to have excellent chemical and thermal stability and a good balance between the mechanical properties of hardness and fracture toughness to enable the production of durable power generation modules. We introduce our research on and development of novel thermoelectric materials consisting of the low-cost and non-toxic elements Al, Fe, and Si. Graphical abstract: Unlabelled Image